Retinoic Acid as a Therapy for Emphysema?. (7th October 2014) - DeLuca, Luigi M.; Ross, Sharon A.
Abstract : In concert with its action as a morphogen during embryonal development, retinoic acid appears to be able to regenerate lung alveoli in an experimental model of elastase-induced emphysema in rats, thereby inhibiting manifestation of the disease. The application to humans is now an interesting possibility.